"Enabling circular business models in the fashion industry: the role of digital innovation". Issue 3 (8th June 2021) - Huynh, Phuc Hong
Abstract : Purpose: Digital innovation and circular business model innovation are two critical enablers of a circular economy. A wide variety of digital technologies such as blockchain, 3D printing, cyber-physical systems, or big data also diverges the applications of digital technologies in circular business models. Given heterogeneous attributes of circular business models and digital technologies, the selections of digital technologies and circular business models might be highly distinctive within and between sectorial contexts. This paper examines digital circular business models in the context of the fashion industry and its multiple actors. This industry as the world's second polluting industry requires an urgent circular economy (CE) transition with less resource consumption, lower waste emissions and a more stable economy. Design/methodology/approach: An inductive, exploratory multiple-case study method is employed to investigate the ten cases of different sized fashion companies (i.e. large, small medium-sized firm (SME) and startup firms). The comparison across cases is conducted to understand fashion firms' distinct behaviours in adopting various digital circular economy strategies. Findings: The paper presents three archetypes of digital-based circular business models in the fashion industry: the blockchain-based supply chain model, the service-based model and the pull demand-driven model. Besides incremental innovations, the radical business model and digital innovations as presented in the pull demand-driven model may be crucial to the fashion circular economy transition. The pull demand–driven model may shift the economy from scales to scopes, change the whole process of how the fashion items are forecasted, produced, and used, and reform consumer behaviours. The paths of adopting digital fashion circular business models are also different among large, SMEs and startup fashion firms. Practical implications: The study provides business managers with empirical insights on how circular business models (CBMs) should be chosen according to intrinsic business capacities, technological competences and CE strategies. The emerging trends of new fashion markets (e.g. rental, subscription) and consumers' sustainable awareness should be not be neglected. Moreover, besides adopting recycling and reuse strategies, large fashion incumbents consider collaborating with other technology suppliers and startup companies to incubate more radical innovations. Social implications: Appropriate policies and regulations should be enacted to enable the digital CE transition. Market patterns and consumer acceptances are considered highly challenging to these digital fashion models. A balanced policy on both the demand and supply sides are suggested. The one-side policy may fail CBMs that entail an upside-down collaboration of both producers and consumers. Moreover, it is perhaps time to rethink how to reduce unnecessary new demand rather than repeatedly producing and recycling. Originality/value: The pace of CE research is lagging far behind the accelerating environmental contamination by the fashion industry. The study aims to narrow the gap between theory and practice to harmonise fashion firms' orchestration and accelerate the transition of the fashion industry towards the CE. This study examines diverse types of digital technologies in different circular business models in a homogeneous context of the fashion industry with heterogeneous firm types.